Amidst the clamor: Effects of emergency department noise on Physicians' health and attention - Taskin, Omer; Disel, Nezihat Rana; Yilmaz, Mustafa (W B Saunders Co-Elsevier Inc, 2024)
Objective: This study aims to assess effects of noise on physicians' stress levels and attention capacities within an emergency department.Methods: In this prospective cross-sectional study, 15 physicians from a state hospital emergency department with 300,000 annual visits provided demographics, work factors, and physiologic data. Attention was evaluated through smartphone-based Stroop tests, while noise and heart rates were monitored via smartwatches. Results: Median physician age was 26, with 16 months' emergency department experience. Average sound intensity was 68.80 dB. Despite noise, physicians in green/yellow areas showed increased Stroop scores (p = 0.002). Heart rate responses correlated with noise changes. End-of-shift surveys highlighted physicians' adaptability and resilience to high noise levels.Conclusion: Noisy emergency departments pose health risks to physicians, but noise-related stress did not significantly affect attention, beneficial for patient care.(c) 2023 Elsevier Inc. All rights reserved.
Keywords: Noise; Emergency department; Stroop test; Sound intensity; Physician